(3TQM MGTjI edG YHO Gddgs - (3eLghds ((3Ndjd Hf eMehO GdehShj GdeQGZjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj dWa HMceJg YLGFH UfYJg (B...(3agPg MbGFb dGFMI hObGFb SGfMI Ydi MGTjI GdefWb aj GdJgPjH GdJj CdagG (B... (3TgGH GdOjf YHO Gddg hGbJUQJ ajgG Ydi eTcdGJgG hJHjjf eaUdGJgG (B...s
(3BNQgG (B:s
... (3bhdfG cd EfSGf MjhGf HGdVQhQI HYV GdEfSGf djS HMjhGf HGdEecGf GdYGe bhdg hJajV GdVQhQI GdSGdH Cj JajV GdVQhQI GdeWdbI (B. (3bO JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs